VD_FINDINFO Jug / 2012 / 275 vom 22. Mai 2012 - VD Tribunal cantonal (2012)
VOLDROIT PÉNAL, BRIGANDAGE, DOMMAGES À LA PROPRIÉTÉDROIT PÉNAL, VIOLATION DE DOMICILE | 139 ch. 1 CP, 140 ch. 1 al. 1 CP, 144 al. 1 CP, 186 CP, 40 CP, 42 CP, 47 CP, 49 ch. 1 CP, 51 CP, 69 CP